Beyond the Trend: Understanding Wardah’s Halal Branding Meaning among Generation Z Consumers in Denpasar - Dewi, Komang Cintya Trisna; Gorda, Anak Agung Ngurah Oka Suryadinatha (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
The rapid development of the halal cosmetic industry in the digital era has generated new dynamics in the construction of halal meaning, particularly among younger generations. Although numerous studies have examined halal as a form of religious certification and a marketing strategy, limited research has explored how halal is interpreted by Muslim minority generations within specific local cultural contexts such as Bali. This study aims to analyze the construction of halal meaning associated with Wardah products among Generation Z consumers in Denpasar City and to examine its implications for brand perception. This research employs a qualitative approach using purposive sampling to select Generation Z informants who use Wardah products in Denpasar. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive data analysis model proposed by Miles and Huberman. The findings reveal that the concept of halal is constructed in a multidimensional manner.